ESG performance, auditing quality, and investment efficiency: Empirical evidence from China - Wang, Wenbing; Yu, Yanyan; Li, Xuan (Frontiers in Psychology, 2022)
Dramatic changes in the business environment have created demands for additional information such as management discussions, governance information, and financial statement notes that go beyond the coverage of traditional financial reporting. Environmental, social, and governance (ESG) information can help gain stakeholder trust, reduce transaction costs, and improve investment efficiency. Taking Chinese A-share listed companies from 2011 to 2020 as a sample, we run fixed effect regressions to test the effect of ESG performance on investment efficiency. ESG performance is measured with the ESG score from the Bloomberg database. The results show that (a) good ESG performance significantly improves investment efficiency, (b) auditing quality partially mediates the relationship between ESG performance and investment efficiency, and (c) the role of ESG performance is stronger in non-state-owned enterprises, undeveloped regions, and firms with low accounting information quality. This paper contributes to the literature on ESG performance and provides references for ESG practice and sustainable corporate development in emerging countries.